Reengineering organizational and technological processes as a factor in improving the quality of construction - Nikoghosyan, N.; Demidova, O.; Litvinenko, A. (Ways to Improve Construction Efficiency, 2019)
The use of reengineering as a means of increasing the competitiveness of construction companies and increasing the efficiency of the construction process is proposed. Reengineering should not be seen as a one-time adjustment of the technological business processes of construction, but as a permanent management to improve business processes. The combination of functional flows, reducing the workflow leads to shorter construction times, lower costs for construction.